Pemberdayaan Petani terhadap Dinamika Petani dalam Beragribisnis Kakao di Kelurahan Nambo Kota Kendari - Abdullah, Sukmawati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
This research aims to know the characteristics that influence the farmer empowerment to dynamics of farmers in cacao agribusiness, to know the efforts that done by farmers in cacao agribusiness and explain the relationship between characteristics of respondents with the efforts done by farmers in cacao agribusiness. The population of this research is a cacao farmer in Nambo Village of Kendari city, totaling 229 cacao farmers. Sampling was done by random sampling, so the sample of research was taken by 60 people (26%) of cacao farmers (Arikunto, 2002). Data of individual factors were analyzed using frequency distributions, and the median. Efforts of farmers in agribusiness cacao analyzed with a tiered scale. The relationship between variables is known by using Rank Order correlation coefficient (Spearman's Rho Rank-Order Correlation), a correlation test for data non-parametric (Sunyoto, 2009), a correlation test for data non-parametric. The results of the research showed that the characteristics of cacao farmers in the Nambo village, the majority are on medium categories, such as age, educational level, number of liability the experience of farming, land tenure, motivation, access to information, and links to the cosmopolitan. Efforts that doing by farmers that showing the dynamics of farmers in agribusiness cacao are: an effort of farmers in agribusiness in the upstream agribusiness subsystem is low, effort of farmers on farm management subsystem is high, and the efforts of farmers in agribusiness on downstream agribusiness subsystem is high, and the characteristics farmers significantly associated with the efforts that done by farmers in cacao agribusiness farmers are farming experience. Farmer characteristics significantly associated with the efforts that done by farmers in agribusiness cacao farmers are motivation, access to information, and to the cosmopolitan nature.